EPIDEMIOLOGICAL AND CLINICAL CHARACTERISTICS OF CHILDREN WITH MEASLES RECEIVING INTRAVENOUS IMMUNOGLOBULIN TREATMENT (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the epidemiological, clinical, and laboratory characteristics of children with measles requiring intravenous immunoglobulin (IVIG) treatment at the Vietnam National Children’s Hospital from January to June 2025.Methods: A retrospective descriptive study was conducted on 111 patients under 18 years of age with confirmed measles diagnosis and IVIG indication, admitted to the Tropical Diseases Center, Vietnam National Children’s Hospital.Results: Children under 9 months of age accounted for 43.2% of the cohort. A total of 81.1% of patients were unvaccinated against measles, including 62.8% in the age-eligible group. Comorbidities were present in 55.9% of patients, predominantly chronic respiratory disease (28.8%) and immunodeficiency (12.6%). The most common clinical features were fever (98.2%), rash (89.2%), cough (69.4%), and conjunctivitis (65.8%). Cytokine storm was the most frequent severe complication (46.8%), followed by shock (21.6%) and rapidly progressive pneumonia (13.5%). Laboratory findings revealed significant organ involvement and systemic hyperinflammation, with mean LDH of 911.7 U/L, mean ferritin of 1,024.0 ng/mL (maximum 20,165 ng/mL), and mean D-dimer of 2,096.8 ng/mL.Conclusions: Pediatric patients with severe measles requiring IVIG at a tertiary referral center are characterized by young age, incomplete vaccination status, high rates of comorbidities, and severe multi-organ dysfunction. Strengthening timely vaccination, early case identification, and prompt therapeutic intervention are essential strategies to reduce the burden of severe measles in children.
Keywords: Measles, intravenous immunoglobulin (IVIG), cytokine storm, Vietnam National Children’s Hospital.